2010
DOI: 10.1002/ajhb.21109
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between adiposity and telomere length: The fels longitudinal study

Abstract: Objectives To assess the relationship between telomere length and adiposity, using dual-energy X-ray absorptiometry (DXA) and magnetic resonance imaging (MRI), in addition to conventional anthropometric proxies including body mass index (BMI) and cardiovascular disease risk factors. Methods A cross-sectional sample of 309 non-Hispanic white participants in the Fels Longitudinal Study aged 8 to 80 yr (52% female) was included. Average telomere length was measured by quantitative PCR. Results Telomere length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
153
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 65 publications
16
153
8
1
Order By: Relevance
“…Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old. 7 Previous studies noticed LTL to be positively associated with physical activity 17 and socioeconomic status 19 and negatively associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old. 7 Previous studies noticed LTL to be positively associated with physical activity 17 and socioeconomic status 19 and negatively associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old. 7 Previous studies noticed LTL to be positively associated with physical activity 17 and socioeconomic status 19 and negatively associated with smoking. 16 However, we did not confirm these results in our study, adjusting for physical activity, education and smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocyte telomere length, which is a widely used biomarker of aging, has been found to be negatively correlated with body mass index (BMI) (3)(4)(5)(6)(7). Although the observed correlation between BMI and telomere length is relatively weak (r = 0.12) (4), it is remarkable that these studies demonstrated that BMI is associated with an age acceleration effect in blood.…”
mentioning
confidence: 97%
“…Similarly, an important aspect of obesity-associated vascular injury obtained from preclinical and clinical studies, is that many of the vascular changes found in obesity are highly similar to those seen with aging [37] , which not only represents a physiological process but in itself represents a strong and independent risk factor for future cardiovascular events [37] . As with aging [37] , experimental or human obesity shows an attenuation of endothelium-dependent vasodilation [38,39] , a decrease in NO bioactivity [38,39] in conjunction with NO synthase uncoupling [37] , an increase in prostanoid-mediated endothelium-dependent contractions [40][41][42] , telomere shortening [43][44][45][46] , increased vascular stiffness [47] , and increased arterial intima-media thickness [26,48] . Obesity also increases tissue levels of endothelin-1 [38,49,50] , a strong vasoconstrictor peptide and atherogenic growth factor and proinflammatory stimulus [51] .…”
Section: Atherosclerosis Begins In Childhoodmentioning
confidence: 99%